Two-particle correlations at high-energy nuclear collisions, peripheral-tube model revisited - Hama, Yogiro; Kodama, Takeshi; Qian, Wei-Liang [UNESP] (Iop Publishing Ltd, 2021)
In this paper, we give an account of the peripheral-tube model, which has been developed to give an intuitive and dynamical description of the so-called ridge effect in two-particle correlations in high-energy nuclear collisions. Starting from a realistic event-by-event fluctuating hydrodynamical model calculation, we first show the emergence of ridge + shoulders in the so-called two-particle long-range correlations, reproducing the data. In contrast to the commonly used geometric picture of the origin of the anisotropic flow, we can explain such a structure dynamically in terms of the presence of high energy-density peripheral tubes in the initial conditions. These tubes violently explode and deflect the near radial flow coming from the interior of the hot matter, which in turn produces a two-ridge structure in single-particle distribution, with approximately two units opening in azimuth. When computing the two-particle correlation, this will result in characteristic three-ridge structure, with a high near-side ridge and two symmetric lower away-side ridges or shoulders. Several anisotropic flows, necessary to producing ridge + shoulder structure, appear naturally in this dynamical description. Using this simple idea, we can understand several related phenomena, such as centrality dependence and trigger-angle dependence.
Keywords: hydrodynamics; heavy-ion nuclear collisions; particle correlation